Enduring bonds : inequality, marriage, parenting, and everything else that makes families great and terrible - Cohen, Philip N. (University of California Press, 2018)
"Modern families provide essential support for happiness and well-being, but they are also engines of inequality, between men and women, between adults and children, and also between those who have supportive families and those who don't. The ability to successfully manage a family life is a modern marker of individual competence, and any failure risks social scorn and stigma. This collection of essays, tied to events in the news and using original demographic data with intuitive graphics, addresses the place of families in our system of inequality, the politics of family structure and change, the role of gender differentiation and segregation in family inequality, and the intersection of families with other forms of inequality"--Provided by publisher